A guide to teaching practice - Cohen, Louis; Manion, Lawrence; Morrison, Keith; Wyse, Dominic (Routledge, 2010)
Keywords: Great Britain; Student teaching; Teachers; Training of

Assimetrias de Género. Ensino e Liderança Educativa - Correia, Ana (Fundação Manuel Leão, 2009)
Keywords: DLCRE

Causation in educational research - Morrison, Keith (Routledge, 2009)
Keywords: Causation; Education; Research

Implementing cross-curricular themes - Morrison, Keith (2018)

Lusofonia, encruzilhadas culturais, Actas da Conferência sobre Lusofonia - Correia, Ana; Sousa, Ivo (Saint Joseph University Press, 2011)

Managing complex change in school: engaging pedagogy, technology, learning and leadership - Garcia, Alejandro Salcedo; Morrison, Keith (Routledge, 2014)
Keywords: EDUCATION / Educational Policy & Reform / General; EDUCATION / Evaluation; EDUCATION / Leadership; Educational change; Educational leadership; Educational technology

Perspectives on Inclusion - Correia, Ana; Couzens, Donna; Ho, Ka Lee Carrie (University of Saint Joseph, 2019)
In an inclusive education system, educators engage with increasing their understanding of individual differences, especially in regard to learning, and develop and adjust learning and assessment tasks and contexts in ways that make them accessible and appropriate for all students regardless of starting ability levels, interests, learning strengths and weaknesses. In inclusive schools, diverse approaches to learning are valued and all learners are challenged and supported to be successful in their learning goals. Macao has begun the journey to develop an increasingly inclusive education system. This book has been written as the journey is beggining and explores some of the different perspectives twoard inclusion and interpretaions of "inclusive education" within Macao's education systems and the wider community at this time. The main aims of the research presented in this book are to understand the different views and roles of staff in Macao schools and in the wider community. The book raises questions about how inclusion in Macao might unfold and identifies areas where efforts may be needed to progress inclusive education.

Replication research in education: a guide to designing, conducting and analysing studies - Morrison, Keith (Routledge, 2022)
"Providing an overview of key issues in theory and practice, Replication Research in Education is designed to identify and discuss the benefits and challenges facing replication studies in education. Both clear and practical, this ground-breaking volume covers how to introduce, develop, conduct, report and discuss these studies, and the issues they raise for policy and practice. Bridging theory and practice, this book considers what replication research should look like, how it should be conducted and how to judge when it has been successful. It enables researchers to plan and conduct studies successfully, from their earliest stages through to completion. This key text: brings together in a single volume, existing issues, claims and counter-claims, discourses and practices of replication introduces, covers, and extends this field of research, indicating its possibilities and limits expands and adds to existing discussions and practices will enable researchers to design, conduct, evaluate and critique studies. The comprehensive and exhaustive coverage of issues and practices within Replication Research in Education make it a "must read" for all novice and experienced educational researchers who are considering, conducting, and reviewing replication studies in education"--

Research Methods in Education - Cohen, Louis; Manion, Lawrence; Morrison, Keith (Routledge, 2007)

Research Methods in Education - Cohen, Louis; Manion, Lawrence; Morrison, Keith (Routledge, 2013)

Research methods in education - Morrison, Keith; Cohen, Louis; Manion, Lawrence (Routledge, 2018)

School leadership and complexity theory - Morrison, Keith (Routledge/Falmer, 2002)
Keywords: Complex organizations; Educational leadership; School management and organization

Student engagement, higher education, and social justice: beyond neoliberalism and the market - Bramley, Corinna; Morrison, Keith (Routledge, 2023)
"Student engagement is a catch-all term, irresistible to educators and policy makers, and serving many agendas and purposes. This ground-breaking book provides a powerful theory of student engagement, rooted in critical theory and social justice. It sets out a compelling argument for student engagement to promote social justice and to repel neoliberalism in, and through, higher education, addressing three key questions: -Student engagement in what? -Student engagement for what? -Student engagement for whom? The answers draw on Habermas, Honneth, Gramsci, Foucault, and Giroux in examining ideology, power, recognition, resistance, and student engagement, with examples drawn from across the world. It sets out key features, limitations and failures of neoliberalism in higher education, and indicates how student engagement can resist it. Student engagement calls for higher education institutions to be sites for challenge, debate on values and power, action for social justice, and for students to engage in the struggle to resist neoliberalism, taking action to promote social justice, democracy, and the public good. This book is essential reading for educators, researchers, managers and students in higher education, social scientists and social theorists. It is a call to reawaken higher education for social justice, human rights, democracy and freedoms"--
Keywords: Active learning; Education, Higher; Neoliberalism; Social aspects; Social justice and education

Suicide prevention in schools: are Macau's teachers prepared? - Días, Javier Suárez; Morrison, Keith (Macau Inter-University Institute, 2005)
Keywords: China Macau (Special Administrative Region); Prevention; Students; Suicidal behavior; Suicide; Teenagers

Taming randomized controlled trials in education: exploring key claims, issues and debates - Morrison, Keith (Routledge, Taylor & Francis Group, 2021)
"There is a recent surge in the use of randomized controlled trials (RCTs) within education globally, with disproportionate claims being made about what they show, 'what works', and what constitutes the best 'evidence'. Drawing on up-to-date scholarship from across the world, Taming Randomized Controlled Trials in Education critically addresses the increased use of RCTs in education, exploring their benefits, limits and cautions, and ultimately questioning the prominence given to them. While acknowledging that randomized controlled trials do have some place in education, the book nevertheless argues that this place should be limited. Drawing together all arguments for and against RCTs in a comprehensive and easily accessible single volume, the book also adds new perspectives and insights to the conversation; crucially, the book considers the limits of their usefulness and applicability in education, raising a range of largely unexplored concerns about their use. Chapters include discussions on: The impact of complexity theory and chaos theory Design issues and sampling in randomized controlled trials Learning from clinical trials Data analysis in randomized controlled trials Reporting, evaluating and generalizing from randomized controlled trials. Considering key issues in understanding and interrogating research evidence, this book is ideal reading for all students on Research Methods modules, as well as those interested in undertaking and reviewing research in the field of education"--
Keywords: Clinical trials; Education; Educational indicators; Research Data processing; Research Methodolgy

《學會閱讀》叢書第一輯 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

《學會閱讀》叢書第二輯 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文兒歌集 -- 果子級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文學習卡 -- 果子級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文學習卡 -- 花兒級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文學習卡 -- 葉芽級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)